Sympathetic activity in breast cancer and metastasis: partners in crime - Conceição, F (2021)
The vast majority of patients with advanced breast cancer present skeletal complications that severely compromise their quality of life. Breast cancer cells are characterized by a strong tropism to the bone niche. After engraftment and colonization of bone, breast cancer cells interact with native bone cells to hinder the normal bone remodeling process and establish an osteolytic “metastatic vicious cycle”. The sympathetic nervous system has emerged in recent years as an important modulator of breast cancer progression and metastasis, potentiating and accelerating the onset of the vicious cycle and leading to extensive bone degradation. Furthermore, sympathetic neurotransmitters and their cognate receptors have been shown to promote several hallmarks of breast cancer, such as proliferation, angiogenesis, immune escape, and invasion of the extracellular matrix. In this review, we assembled the current knowledge concerning the complex interactions that take place in the tumor microenvironment, with a special emphasis on sympathetic modulation of breast cancer cells and stromal cells. Notably, the differential action of epinephrine and norepinephrine, through either a- or ß-adrenergic receptors, on breast cancer progression prompts careful consideration when designing new therapeutic options. In addition, the contribution of sympathetic innervation to the formation of bone metastatic foci is highlighted. In particular, we address the remarkable ability of adrenergic signaling to condition the native bone remodeling process and modulate the bone vasculature, driving breast cancer cell engraftment in the bone niche. Finally, clinical perspectives and developments on the use of ß-adrenergic receptor inhibitors for breast cancer management and treatment are discussed.